Pendidikan literasi komunikasi kesehatan dalam pencegahan babyblues syndrome dan postpartum depression - Wahyu Utamidewi; Yanti Tayo; Pamungkas Satya Putra; Mohamad Febrianto; Achmad Naufal Hafidz (Jurnal Komunikasi Profesional, 2022)
Mood issues are often seen during childbirth. These mood disorders may vary in severity from moderate to severe, such as the baby blues syndrome and postpartum depression. Postpartum depression is a more severe kind of mood illness than the baby blues syndrome and may impair mothers' ability to perform their duties and care for their infants. Postpartum moms' lack of understanding regarding baby blues syndrome and postpartum depression, or at the very least the lack of information owned by mothers, may have an effect on factors affecting postpartum mental health. This circumstance makes it more difficult for new moms to get more information, particularly concerning the baby blues and postpartum depression. The program, which is provided by a team of academics and students, aims to provide counseling on health communication literacy in order to avoid baby blues and postpartum depression. This community service team is made up of three leactures and numerous students from Singaperbangsa Karawang University's Department of Communication Studies. This therapy is designed to boost postpartum moms' understanding and awareness of the critical nature of mental health. The team conducted a pretest before to therapy and a posttest after counseling to see how much the mother's knowledge on preventing baby blues syndrome and postpartum depression improved. Following outreach initiatives, it can be stated that pregnant women now have a greater understanding of how to avoid baby blues syndrome and postpartum depression